2009
DOI: 10.1186/1758-2555-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of movement training on upper limb motor strategies in persons with shoulder impingement syndrome

Abstract: Background: Movement deficits, such as changes in the magnitude of scapulohumeral and scapulathoracic muscle activations or perturbations in the kinematics of the glenohumeral, sternoclavicular and scapulothoracic joints, have been observed in people with shoulder impingement syndrome. Movement training has been suggested as a mean to contribute to the improvement of the motor performance in persons with musculoskeletal impairments. However, the impact of movement training on the movement deficits of persons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…Of particular interest are the relative contributions of the serratus anterior and trapezius muscles that stabilize the scapula and induce scapular motion necessary for humeral elevation (Bagg and Forrest, 1988;Johnson and Pandyan, 2005;Kronberg et al, 1990). Abnormal scapular neuromuscular control, demonstrated by excess EMG mean activity of the upper trapezius, decreased mean activity of the serratus anterior (Ludewig and Cook, 2000), and altered EMG onset timing in the lower trapezius and serratus anterior muscles, has been found in individuals with shoulder pain associated with impingement (Cools et al, 2007(Cools et al, , 2003(Cools et al, , 2005Roy et al, 2009b;Wadsworth and Bullock-Saxton, 1997). Given these findings, therapeutic interventions that address an imbalance in scapular muscle neuromuscular activity and control rather than purely muscle strength have been advocated in evidence-based shoulder rehabilitation and injury prevention programs (Kuhn, 2009;Ludewig and Borstad, 2003;Reinold et al, 2009;Roy et al, 2009a;Tate et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Of particular interest are the relative contributions of the serratus anterior and trapezius muscles that stabilize the scapula and induce scapular motion necessary for humeral elevation (Bagg and Forrest, 1988;Johnson and Pandyan, 2005;Kronberg et al, 1990). Abnormal scapular neuromuscular control, demonstrated by excess EMG mean activity of the upper trapezius, decreased mean activity of the serratus anterior (Ludewig and Cook, 2000), and altered EMG onset timing in the lower trapezius and serratus anterior muscles, has been found in individuals with shoulder pain associated with impingement (Cools et al, 2007(Cools et al, , 2003(Cools et al, , 2005Roy et al, 2009b;Wadsworth and Bullock-Saxton, 1997). Given these findings, therapeutic interventions that address an imbalance in scapular muscle neuromuscular activity and control rather than purely muscle strength have been advocated in evidence-based shoulder rehabilitation and injury prevention programs (Kuhn, 2009;Ludewig and Borstad, 2003;Reinold et al, 2009;Roy et al, 2009a;Tate et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…It has been recently hypothesized that reorganization of the somatosensory and motor cortices could explain part of the deficits associated with RC tendinopathy (Myers et al, 2006;Roy et al, 2009;van Vliet and Heneghan, 2006). This reorganization could also explain the chronicity of the symptoms and the lack of treatment effectiveness for one third of patients.…”
Section: Introductionmentioning
confidence: 96%
“…Based on this, normal movement can be achieved without inflammation and pain of the subacromial tissue 16,17) . reported that intervention based on motor control theory for SIS patients changed the quality of the activity of the shoulder bones and muscles and it improved the abnormal movement and instability of the glenohumeral and scapulothoracic motion and the sternoclavicular joint 18) . From the kinetical aspect, this result showed an improved ability to control movement and the importance of exercise control as an intervention for SIS patients.…”
Section: Introductionmentioning
confidence: 99%